2022
DOI: 10.1159/000524332
|View full text |Cite
|
Sign up to set email alerts
|

Das Beste aus zwei Welten: Eine systematische Übersicht zu Faktoren der Implementierung einer “Blended Therapy” (Gemischte Therapie) in der Psychotherapeutischen Routineversorgung

Abstract: <b><i>Ziel:</i></b> Diese Arbeit gibt einen Überblick über bisherige wissenschaftliche Empfehlungen zur Implementierung der blended therapy, d.h. der Kombination von Therapien in Präsenz und via digitaler Medien. Die Empfehlungen um­fassen die Themen: (1) wahrgenommene Barrieren von Psychotherapeut*innen, (2) Format der blended therapy und (3) Indikationen für Patient*innen. In diesem Rahmen werden Faktoren aufgezeigt, die Akteur*innen im Gesundheitssystem als Orientierung dienen können… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…To ensure the uptake of a BC intervention, it seems necessary to think about specific requirements psychotherapists of all therapeutic approaches have for an IBI that they can optimally integrate into their practice. Results of a systematic review by Dech et al (2022) showed that the incorporation of online content into routine psychotherapeutic care requires a restructuring of the way psychotherapists work and is often initially associated with an increased workload. They concluded that barriers for BC should be assessed and addressed, and psychotherapists should be involved in the implementation process to increase acceptability and feasibility.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the uptake of a BC intervention, it seems necessary to think about specific requirements psychotherapists of all therapeutic approaches have for an IBI that they can optimally integrate into their practice. Results of a systematic review by Dech et al (2022) showed that the incorporation of online content into routine psychotherapeutic care requires a restructuring of the way psychotherapists work and is often initially associated with an increased workload. They concluded that barriers for BC should be assessed and addressed, and psychotherapists should be involved in the implementation process to increase acceptability and feasibility.…”
Section: Introductionmentioning
confidence: 99%